Upaya Peningkatan Kompetensi Guru dalam Pendampingan Kegiatan Ekstra Kurikuler di SD Teladan Metro - Jamaluddin, Jamaluddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
Good teaching and learning activities must contain three main points, namely planning, implementation, and evaluation. A teacher is required to plan, implement and evaluate the learning process. The learning planning includes preparing learning tools such as syllabus. The syllabus is a minimal device must be prepared by the teacher before implementing the learning process - including preparing a syllabus for extra-curricular activities for students at school. In fact, there are low levels of teachers' guidance in extra-curricular activity to their students. This research was conducted to reveal how far is headmasters' roles in improving the teachers' competency in preparing and implementing extracurricular activities for students.